2018
DOI: 10.1158/1940-6207.capr-18-0188
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Tomato Powder Inhibits High-Fat Diet–Promoted Hepatocellular Carcinoma with Alteration of Gut Microbiota in Mice Lacking Carotenoid Cleavage Enzymes

Abstract: Both incidence and death rate due to liver cancer have increased in the United States. Higher consumption of lycopene-rich tomato and tomato products is associated with a decreased risk of cancers. b-Carotene-15, 15 0 -oxygenase (BCO1), and b-carotene-9 0 , 10 0 -oxygenase (BCO2) cleave lycopene to produce bioactive apo-lycopenoids. Although BCO1/BCO2 polymorphisms affect human and animal lycopene levels, whether dietary tomato consumption can inhibit high-fat diet (HFD)-promoted hepatocellular carcinoma (HCC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 58 publications
1
44
0
Order By: Relevance
“…Intestinal microbiota plays a major role in the breakdown, absorption and metabolism of key dietary constituents contributing, for example, to the transformation of compounds to bioactive components [43] as is the case with the metabolization of 9-Z-β-carotene to its respective retinoic acid. It has also been shown that some foods, owing to their content in certain nutrients including carotenoids, are able to regulate intestinal microbiota and lower the risk of several chronic diseases [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal microbiota plays a major role in the breakdown, absorption and metabolism of key dietary constituents contributing, for example, to the transformation of compounds to bioactive components [43] as is the case with the metabolization of 9-Z-β-carotene to its respective retinoic acid. It has also been shown that some foods, owing to their content in certain nutrients including carotenoids, are able to regulate intestinal microbiota and lower the risk of several chronic diseases [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme β-carotene oxygenase 1 (BCO1) is a carotenoid lyase that was reported to be associated with a high consumption of tomato and tomato products rich in lycopene. BCO1 can cleave lycopene to produce carotenoids (39). However, there was also evidence that BCO1 is stably expressed in NB cells, and the expression of this gene inhibits the self-renewal and labeling of neuroblastoma CSC by regulating related miRNA (40).…”
Section: Discussionmentioning
confidence: 99%
“…Tomato intake may also decrease risk of HCC through increased gut microbial diversity, as NASH is related to gut dysbiosis and progression to HCC 28,29 . In β-carotene-15, 15'-oxygenase (BCO1) and β-carotene-9', 10'oxygenase (BCO2) knockout mice assigned to high-fat diet with or without tomato powder for 24 weeks, tomato powder significantly reduced the incidence of HCC by 67% along with decreased hepatic inflammatory foci 30 . Taken together, these experimental data suggested that tomato rather than lycopene offered protective effect against the promoting effect of alcohol and high-fat diet on chemical carcinogen induced carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%